Efficacy and Safety of Cryobiopsy vs. Forceps Biopsy for Interstitial Lung Diseases, Lung Tumors, and Peripheral Pulmonary Lesions: An Updated Systematic Review and Meta-Analysis - Giri, Mohan; Huang, Guichuan; Puri, Anju; Zhuang, Rongjuan; Li, Yishi; Guo, Shuliang (Frontiers in Medicine, 2022)
Background: Cryobiopsy has emerged a novel alternative to conventional forceps biopsy for the diagnosis of for interstitial lung diseases (ILD), lung tumors and peripheral pulmonary lesions (PPLs). This study aims to compare cryobiopsy and forceps biopsy for diagnosis of these lung pathologies with respect to efficacy and safety by performing a meta-analysis of updated evidence. Methods: PubMed, Embase, Web of Science, the Cochrane Library, OVID, CNKI and Wanfang databases were searched for eligible studies. Randomized and non-randomized comparative studies investigating efficacy and safety of cryobiopsy versus forceps biopsy for lung pathologies were included. Pooled results were calculated as an odds ratio (OR) or standardized mean difference (SMD) with 95 % confidence interval. Results: A total of 39 studies, including 9 RCTs with 3586 biopsies (1759 cryobiopsies and 1827 flexible forceps biopsies) were analyzed. Cryobiopsy was associated with a significant increase in the diagnostic rates of ILDs (OR, 4.29; 95% CI, 1.85-9.93; P<0.01), lung tumors (OR, 3.58; 95% CI, 2.60-4.93; P<0.01), and PPLs (OR, 1.70; 95% CI, 1.23-2.34; P<0.01). Cryobiopsy yielded significantly larger specimens compared to flexible forceps biopsy (SMD, 3.06; 95% CI, 2.37-3.74; P<0.01). The cryobiopsy group had a significantly higher moderate to severe bleeding risk than the forceps group (OR, 2.17; 95% CI, 1.48-3.19; P<0.01). No significant difference was observed in the incidence of pneumothorax between the groups (OR, 0.90; 95% CI, 0.44-1.85; P=0.78). Conclusion: Our results demonstrate that cryobiopsy is a safe and efficacious alternative to conventional forceps biopsy.